Retinal and choroidal blood flow changes in dialysis patients assessed by wide-field swept-source optical coherence tomography angiography - Li, Wan; Zhou, Qing; Ni, Jiulin; Pan, Xun; Li, Min; Hua, Fei; Tang, Huan; Li, Shuting (Frontiers in Medicine, 2025)
PurposeThe study utilized wide-field swept-source optical coherence tomography angiography (SS-OCTA) to examine the alterations in retinal and choroidal blood flow in patients with end-stage renal disease (ESRD) before and after hemodialysis.MethodsForty-two eyes of 24 participants with end-stage renal disease were enrolled in this prospective and cross-sectional study. A full ophthalmic examination was conducted on each participant 1 h before and after hemodialysis, which included wide-field SS-OCTA imaging on OCTA scans measuring 9 mm x 9 mm. The mean perfusion area (PA), superficial vessel density (SVD), retinal inner VD (RIVD), and choroidal vascularity index (CVI) were evaluated independently before and after hemodialysis in both macular and optic disk areas across all 16 sectors defined by the Early Treatment Diabetic Retinopathy Study (ETDRS).ResultsThe study subjects consisted of 18 men and 6 women, comprising 9 patients with diabetic renal failure and 23 patients with hypertension. The mean age of the patients with end-stage renal disease was 57.3 ± 12.7 years. In the central ring, retinal inner VD were significantly decreased after HD (p < 0.05), but there were no significant differences in the average PA,SVD, and CVI between before and after single HD session. In the 3 mm radius, inferior quadrant of macular retinal inner VD, PA of the macular and optic disk were significantly decreased after HD (p < 0.05). In the 6 mm radius, the temporal section of the retinal inner VD, nasal and inferior of PA were noticeably reduced in the HD group. In the wide-field scans (9 mm radius), there was exhibited a more pronounced reduction in inferior PA, SVD and retinal inner VD of optic disk area in inferior sectors after HD. Fairly consistent CVI values were noted in the macular zone, except for a statistically significant decrease in the temporal quadrant at 3 mm and 6 mm within the optic disk area (p = 0.040 and 0.048, respectively).ConclusionResults revealed a more significant decrease in indicators of the choroid and optic disk area compared to the inner retina and macular zone. Wide-field SS-OCTA displays potential as an imaging technique for early detection of microcirculation changes in hemodialysis patients.